A high-throughput screen identifies that CDK7 activates glucose consumption in lung cancer cells - Chiara Ghezzi (Nature Portfolio, 2019)
Many cancer cells have increased glucose consumption compared to normal cells, a feature that can be exploited therapeutically. Here, the authors carry out a chemical screen and identify compounds that selectively blocks glucose metabolism in non-small-cell lung cancer cell lines.